2002
DOI: 10.1080/01446190210123826
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of market orientation in chartered surveying firms

Abstract: This study tests marketing theory concerning market orientation in the context of the chartered surveying industry. Using data collected in a mail survey from 179 UK general practice chartered surveying firms, it is found that firms with more risk tolerant senior managers and more formalized and specialized marketing organization structures have higher levels of market orientation. The data indicate also that market orientation positively impacts firms' business and marketing performance, and that this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The current study provides a guide to anyone interested in learning about MO and its impact on performance as well as factors that drive Narver & Slater (1990), , Slater & Narver (1994), Greenley (1995), Kumar, Subramanian, & Yauger (1998), Appiah-Adu (1998, Bhuian (1998), Avlonitis & Gounaris (1999), Pulendran, Speed, & Widing (2000, Harris (2001), Grewal & Tansuhaj (2001), Ngansathil (2001), Subramanian & Gopalakrishna (2001), Cadogan, Diamantopoulos, & Siguaw (2002), Tay & Morgan (2002), Rose & Shooham (2002), Langerak (2003), Kirca et al (2005), Cadogan et al (2006), Dwairi et al (2007), Augusto & Coelho (2007), Olavarrieta & Friedmann (2007), Sørensen (2007) Business strategy Pelham (1997), Matsuno & Mentzer (2000), Langerak (2003), Kumar et al (2011) 6 Size of firm Llonch & Walino (1996), Barret & Weinstein (1999), Pelham (2000), Raju, Lonial, Gupta, & Ziegler (2000), Hult, Hurley, & Knight (2003), Lüneborg & Nielsen (2003), Song & Parry (2009), Li & Zhou (2010, Kirca (2011) 7 Learning orientation Baker & Sinkula (1999a), Noble et al (2002) 8 Culture Pitt, Caruana, & Berthon (1996), S...…”
Section: Resultsmentioning
confidence: 97%
“…The current study provides a guide to anyone interested in learning about MO and its impact on performance as well as factors that drive Narver & Slater (1990), , Slater & Narver (1994), Greenley (1995), Kumar, Subramanian, & Yauger (1998), Appiah-Adu (1998, Bhuian (1998), Avlonitis & Gounaris (1999), Pulendran, Speed, & Widing (2000, Harris (2001), Grewal & Tansuhaj (2001), Ngansathil (2001), Subramanian & Gopalakrishna (2001), Cadogan, Diamantopoulos, & Siguaw (2002), Tay & Morgan (2002), Rose & Shooham (2002), Langerak (2003), Kirca et al (2005), Cadogan et al (2006), Dwairi et al (2007), Augusto & Coelho (2007), Olavarrieta & Friedmann (2007), Sørensen (2007) Business strategy Pelham (1997), Matsuno & Mentzer (2000), Langerak (2003), Kumar et al (2011) 6 Size of firm Llonch & Walino (1996), Barret & Weinstein (1999), Pelham (2000), Raju, Lonial, Gupta, & Ziegler (2000), Hult, Hurley, & Knight (2003), Lüneborg & Nielsen (2003), Song & Parry (2009), Li & Zhou (2010, Kirca (2011) 7 Learning orientation Baker & Sinkula (1999a), Noble et al (2002) 8 Culture Pitt, Caruana, & Berthon (1996), S...…”
Section: Resultsmentioning
confidence: 97%
“…Market orientation is frequently claimed to improve organisational performance on the basis that organisations that are market-oriented are better able to track and respond to customer needs and preferences, and can therefore better satisfy customers and hence perform at higher levels (Kolar, 2006;Tay and Morgan, 2002;Ramaseshan et al, 2002;Lafferty and Hult, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A further analysis of the breakdown of the overall MO model to three component models revealed that the MO of large retailers mainly lies IJRDM 38,5 in the aspects of ID (b ¼ 0.35, p , 0.01) and RESP (b ¼ 0.28, p , 0.05). This is probably because larger retailers are more experienced in information acquisition, distribution, and utilization (Sinkula, 1994) and are more formalized, with rules and policies in place to implement interdepartmental or cross-functional communication and an established mechanism to respond to a changing market (Tay and Morgan, 2002). In addition, larger businesses have more resources than small firms, which inhibit small retailers from dedicating human and financial resources to market-oriented activities.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Jaworski and Kohli (1993) suggested that centralization and formalization might encourage response implementation. Tay and Morgan (2002) concluded that formalization is positively related to MO. Therefore, we believe that retailers' use of buying committees facilitates the development of MO in China because the formalization of procedures can help collect and distribute market information systematically and the centralization of the decision-making process may accelerate market responsiveness.…”
Section: Retailer Firm Size and Momentioning
confidence: 99%